PENGARUH APLIKASI PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) PADA PERTUMBUHAN TANAMAN KACANG HIJAU DENGAN MEDIA TANAM YANG BERBEDA - Rifdah Aprianti; Nur Laili; Eko Handayanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
Green bean plants are still used as side plants, yet the technique of green bean cultivation has not been done optimally. The advantages of green bean plants is that the plant can be planted in less fertile soil conditions such asÂ Ultisols.Â This srtudy was aimed to elucidate the effect of application biofertilizer (plant growth proting rhizobacteria (PGPR) on growth of geen bean on an Ultisol. Treatments tested were combinations of soil (soil only =T1, soil + kompos =T2), and biofertilizer (H0=no bifertilizer, H1: biofertilizer of formula 1, H2: biofrtilizer of formula 2, and H3: Beyonic StarTmik biofertilizer). Results of the study showed that T2H2 treatment could increase population of N fixing bacteria, respiration, soil pH, and soil enzymes, T2H0 treatment could increase C-organic (5.46%), and T2H3 treatment could increase available N in the soil. T2H3 treatment gave the best growth of geen bean.